Involvement of PSMD10, CDK4, and Tumor Suppressors in Development of Intrahepatic Cholangiocarcinoma of Syrian Golden Hamsters Induced by Clonorchis sinensis and N-Nitrosodimethylamine - Uddin, Md. Hafiz; Choi, Min-Ho; Kim, Woo Ho; Jang, Ja-June; Hong, Sung-Tae (PLOS Neglected Tropical Diseases, 2015)
Background Clonorchis sinensis is a group-I bio-carcinogen for cholangiocarcinoma (CCA). Although the epidemiological evidence links clonorchiasis and CCA, the underlying molecular mechanism involved in this process is poorly understood. In the present study, we investigated expression of oncogenes and tumor suppressors, including PSMD10, CDK4, p53 and RB in C. sinensis induced hamster CCA model. Methods Different histochemical/immunohistochemical techniques were performed to detect CCA in 4 groups of hamsters: uninfected control (Ctrl.), infected with C. sinensis (Cs), ingested N-nitrosodimethylamine (NDMA), and both Cs infected and NDMA introduced (Cs+NDMA). The liver tissues from all groups were analyzed for gene/protein expressions by quantitative PCR (qPCR) and western blotting. Principal Findings CCA was observed in all hamsters of Cs+NDMA group with well, moderate, and poorly differentiated types measured in 21.8% ± 1.5%, 13.3% ± 1.3%, and 10.8% ± 1.3% of total tissue section areas respectively. All CCA differentiations progressed in a time dependent manner, starting from the 8th week of infection. CCA stroma was characterized with increased collagen type I, mucin, and proliferative cell nuclear antigen (PCNA). The qPCR analysis showed PSMD10, CDK4 and p16INK4 were over-expressed, whereas p53 was under-expressed in the Cs+NDMA group. We observed no change in RB1 at mRNA level but found significant down-regulation of RB protein. The apoptosis related genes, BAX and caspase 9 were found downregulated in the CCA tissue. Gene/protein expressions were matched well with the pathological changes of different groups except the NDMA group. Though the hamsters in the NDMA group showed no marked pathological lesions, we observed over-expression of Akt/PKB and p53 genes proposing molecular interplay in this group which might be related to the CCA initiation in this animal model. Conclusions/Significance The present findings suggest that oncogenes, PSMD10 and CDK4, and tumor suppressors, p53 and RB, are involved in the carcinogenesis process of C. sinensis induced CCA in hamsters.